2009
DOI: 10.1051/0004-6361/200912608
|View full text |Cite
|
Sign up to set email alerts
|

The RMS survey

Abstract: Context. The red MSX source (RMS) survey has identified a large sample of candidate massive young stellar objects (MYSOs) and ultra compact (UC) HII regions from a sample of ∼2000 MSX and 2MASS colour selected sources. Aims. To search for H 2 O masers towards a large sample of young high mass stars and to investigate the statistical correlation of H 2 O masers with the earliest stages of massive star formation. Methods. We have used the Mopra Radio telescope to make position-switched observations towards ∼500 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…CS (Bronfman et al 1996) and H 2 O maser emission (Urquhart et al 2009) are reported close to the source location. The RMS catalogue provides a distance of 3.9 kpc and a bolometric luminosity of 9 × 10 3 L .…”
Section: B9 Iras 15450-5431mentioning
confidence: 65%
See 1 more Smart Citation
“…CS (Bronfman et al 1996) and H 2 O maser emission (Urquhart et al 2009) are reported close to the source location. The RMS catalogue provides a distance of 3.9 kpc and a bolometric luminosity of 9 × 10 3 L .…”
Section: B9 Iras 15450-5431mentioning
confidence: 65%
“…CS emission (Bronfman et al 1996), OH (Caswell 1998), CH 3 OH (Green et al 2012) and H 2 O (Urquhart et al 2009) masers are detected on the source and in its surroundings. Faúndez et al (2004) detected the continuum emission from the source at 1.2 mm, and estimated L bol = 7.1 × 10 4 L and M c = 1.1 × 10 3 M from SED analysis.…”
Section: B4 Iras 13484-6100mentioning
confidence: 94%
“…We get 2 ± 1 kpc for the spectrophotometric distance. Some Hii regions and YSOs with measured RVs are found near the cluster (Urquhart et al 2007(Urquhart et al , 2009). On average, we get a kinematic distance to the system of 4.3 kpc, which is in agreement with our spectroscopic distance.…”
Section: Vvv Cl036mentioning
confidence: 93%
“…The Red MSX Source (RMS) survey (Lumsden et al 2002;Mottram et al 2011) contains a large list of objects measured in 2MASS, MSX, Spitzer, and reprocessed IRAS/IGAL images for objects along the Galactic plane, including ultra-compact (UC) H ii regions and a large sample of MYSOs. Additional observations were used to separate the MYSOs from UCH iis, such as water masers (Urquhart et al 2009b(Urquhart et al , 2011 and centimetric emission (Urquhart et al , 2009a. Recently, the bolometric fluxes of those sources were derived by Mottram et al (2011) using IR and submillimetric data and adopting the kinematic distances derived by CO observations from Urquhart et al ( , 2008 and a spectral energy distribution (SED) model.…”
Section: Introductionmentioning
confidence: 99%